Berberine Suppresses Leukocyte Adherence by Downregulating CX3CL1 Expression and Shedding and ADAM10 in Lipopolysaccharide-Stimulated Vascular Endothelial Cells - Wu, Yi-Hong; Wei, Chen-Ying; Hong, Wei-Chin; Pang, Jong-Hwei Su (International journal of molecular sciences, 2022)
Berberine exerts therapeutic effects in inflammation-associated diseases. In a lipopolysaccharide (LPS)-induced endotoxemic acute lung injury (ALI) rat model, berberine alleviated lung injury through different anti-inflammatory mechanisms; however, treatment effects on CX3CL1 expression and shedding remain to be examined. As these processes play important roles in promoting the binding of leukocytes to the endothelium, the CX3CL1/CX3CR1 axis and its related pathways may serve as potential targets for the clinical treatment of ALI. The anti-inflammatory effects of berberine were investigated in LPS-stimulated rats, human umbilical cord vein endothelial cells (HUVECs), and THP-1 monocytic cells. Cx3cl1 expression in rat pulmonary tissues was examined using immunohistochemistry. CX3CL1, CX3CR1, RELA, STAT3, and ADAM10 levels were examined using Western blotting. CX3CL1 and ADAM10 mRNA levels were examined using quantitative real-time polymerase chain reaction. Soluble fractalkine levels in LPS-stimulated rats and HUVECs were examined using the enzyme-linked immunosorbent assay. Berberine significantly mitigated the LPS-induced upregulation of fractalkine and soluble fractalkine in rats and cultured HUVECs. Berberine mitigated the LPS-induced activation of the NF-κB and STAT3 signaling pathways. In THP-1 cells, berberine mitigated the LPS-induced upregulation of CX3CR1. Furthermore, the membrane expression of ADAM10 in LPS-stimulated HUVECs was suppressed by the berberine treatment. Berberine dose-dependently inhibited the LPS-induced activation of the CX3CL1/CX3CR1 axis and fractalkine shedding through ADAM10. These findings reveal a novel molecular mechanism underlying the inhibitory effect of berberine on monocyte adherence to the endothelium during inflammation.